A percepção de gestores e professores da Rede Pública Municipal de Ensino de Cascavel-PR sobre os impactos do artigo 14 do FUNDEB Permanente no contexto escolar - Zucco, Gabriela Viana (2025)
With the enactment of Federal Law No. 14,113 on December 25, 2020, which established the Permanent FUNDEB and defined the conditions set forth in its Article 14, namely: (i) appointment of school principals based on performance and merit criteria; (ii) participation of at least 80% of regularly enrolled students in SAEB large- scale assessments; (iii) reduction of educational, racial, and economic inequalities; (iv) a collaborative system between states and municipalities through the redistribution of ICMS tax revenues, giving rise to ICMS-Education; and (v) curriculum alignment with the National Common Core Curriculum (BNCC). As a result, the outcomes of external assessments became directly linked to the redistribution of financial resources, whether through the federal government’s VAAR supplement or ICMS-Education. Consequently, states, municipalities, and the Federal District reorganized themselves to comply with these conditions and secure the funding.Thus, the research problem is: according to the perception of school principals, pedagogical coordinators, and teachers, what are the impacts of Article 14 on management, school organization, and the teaching and learning process within the Municipal Public Education System of Cascavel/PR? The general objective is to analyze the extent to which financing (Permanent FUNDEB), conditioned on indicators of improvement in school management quality and student learning outcomes measured by SAEB, affects management, school organization, and the teaching and learning process in Cascavel’s Municipal Public Education System. To achieve the proposed objectives, a qualitative approach was adopted. The research was conducted through a literature review (Freitas, 2018; Gentili, 1996; Frigotto, 1989; Pinto, 2000; 2002; 2005; 2012; 2018; 2019; Amaral, 2012; Peroni, 1999; 2013; 2016; 2020; Bardin, 1977); documentary analysis (Law No. 14,113/2020; Constitutional Amendment No. 108/2020; statistical reports from Cascavel’s Municipal Public Education System, as well as ministerial ordinances and QEdu data on student proficiency); and field research using questionnaires remotely answered via Google Forms by school administrators and 5th-grade teachers who met the participation criteria. Based on participants’ perceptions, it is possible to identify certain impacts of Article 14 of the Permanent FUNDEB within the school context. These impacts reveal contradictory processes that permeate education, undermining its educational and emancipatory nature by tying funding to external assessments of schooling, without effectively resulting in improved educational quality.